Antimicrobial and cytotoxic effects of endophytic Streptomyces strains isolated from Cinnamomum cassia Presl in Vietnam - Quang Huy, Nguyen; Thi Hanh Nguyen, Vu; Van The, Nguyen; Thi Lien, Bui; Thi Thu Hang, Le; Quyet Tien, Phi (Vietnam Journal of Biotechnology, 2020)
Vietnam is recognized as one of the countries with the high diversity of medicinal plant species in the world, nevertheless little is known about the distribution, diversity and biological activity of endophytic actinomycetes associated with host plants. The present study aimed to evaluate antimicrobial and cytotoxic activities of four endophytic Streptomyces strains including Streptomyces sp. HBQ75, HBQ87, HBQ102 and HBQ104 isolated from different organs (roots, stems or leaves) of Cinnamomum cassia Presl. Analysis of 16S rRNA gene sequences and the phylogenetic tree assigned them to four different Streptomyces species as follow Streptomyces fulvissimus HBQ75, Streptomyces parvulus HBQ87, Streptomyces pratensis HBQ102 and Streptomyces ribosidificus HBQ104. These strains exhibited broad antimicrobial spectrum against at least five out of nine pathogens tested, among them S. parvulus HBQ87 showed the best activity (inhibition zones >20 mm). Interestingly, S. parvulus HBQ87 carried all three genes (pks-I, pks-II and nrps) encoding for polyketide synthase or non-ribosomal peptide synthetase enzymes involved in biosynthesis of secondary metabolites, while the remaining strains only possessed one or two genes. All the Streptomyces strains were positive for the anthracyclines-like antibiotic activity. The cell-free supernatants of S. parvulus HBQ87 revealed remarkable inhibitory effects against all three human cacinomar cell lines including hepatoma Hep3B, breast adenocarcinoma MCF7 and lung cancer A549 cells at both concentrations tested (30 µg/mL and 100 µg/mL), while S. fulvissimus HBQ75 and S. pratensis HBQ102 were active against only Hep3B and MCF7 cells. In conclusion, the phenotypic and genotypic features of the four endophytic Streptomyces strains suggest that they have a capacity to produce different broad-spectrum secondary metabolites. Among them, S. parvulus HBQ87 could be the most potential candidate for the production of important antimicrobial and antitumor compounds.